2018
DOI: 10.1016/j.chiabu.2017.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Does parental substance use always engender risk for children? Comparing incidence rate ratios of abusive and neglectful behaviors across substance use behavior patterns

Abstract: Parental substance use disorder (SUD) is associated with an added risk for child abuse and neglect, but less is understood about how a range of parental use behaviors is associated with differential maltreatment frequencies. This study used the National Survey of Child and Adolescent Well-Being (NSCAW I) to create categories for parental substance use behaviors that are conceptually associated with varying levels of substance-related impairments. The study sample was composed of 2100 parents of children ages 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 45 publications
3
22
1
2
Order By: Relevance
“…Past-year alcohol use (but not lifetime alcohol use) was associated with higher frequencies of all types of discipline, ranging from nonviolent discipline to physical abuse compared with no alcohol use. These findings align with prior work observing that past-year parental alcohol use is associated with higher annual frequency of abusive behaviors and extends this to the full range of parental discipline approaches (Freisthler et al, 2014;Freisthler & Wolf, 2016;Kepple, 2018). Our study also observed a significant bivariate relationship between a history of methamphetamine use and physical abuse, without including alcohol use.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Past-year alcohol use (but not lifetime alcohol use) was associated with higher frequencies of all types of discipline, ranging from nonviolent discipline to physical abuse compared with no alcohol use. These findings align with prior work observing that past-year parental alcohol use is associated with higher annual frequency of abusive behaviors and extends this to the full range of parental discipline approaches (Freisthler et al, 2014;Freisthler & Wolf, 2016;Kepple, 2018). Our study also observed a significant bivariate relationship between a history of methamphetamine use and physical abuse, without including alcohol use.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have investigated the relationship between specific types of substances and punitive parenting based on the prior rationale that substances vary in degree of potential harm to the individual user and to the child; however, they have typically evaluated correlations between one parenting outcome measure and parental use of one type of substance. For example, studies have observed a relationship between alcohol use and physical abuse frequency for light to moderate levels of drinking and heavy drinking in both high-risk child welfare and general population samples (Freisthler, Holmes, & Wolf, 2014;Freisthler & Wolf, 2016;Kepple, 2018). It may be that alcohol use-related effects-such as disinhibition even at low levels of drinking (Oscar-Berman & Marinković, 2007)-can increase disciplinary or aggressive parenting behaviors relative to nonusers.…”
Section: Punitive Parenting By Type Of Drugmentioning
confidence: 99%
“…Apart from a genetic factor in families with psychoactive substance, deficient parenting and the frequent occurrence of neglect and abuse constitute a risk for the children to develop substance use. Epigenetic mechanisms are also thought to be involved (30).…”
Section: Discussionmentioning
confidence: 99%
“…En este sentido, Staton y su grupo encontraron una asociación sistemática con tasas más altas de derivaciones a sistemas de protección infantil por abuso físico y por negligencia. 29,30 También se identificó alteración en el vínculo con los hijos y el uso de sustancias puesto que los padres con adicción suelen encontrar difícil mantener las tareas y rutinas del hogar, como consecuencia de los síntomas de intoxicación y abstinencia. Además, experimentan dificultades financieras, renuncian a comprar artículos básicos o experimentan cambios de humor que afectan su capacidad para atender las necesidades de sus hijos.…”
Section: Materials Y Métodosunclassified